Is an Appeal to Popularity a Fallacy of Popularity? - Dedrick, Don (Informal Logic, 2019)
It is common to view appeals to popularity as fallacious. We argue this is a mistake and that Condorcet’s jury theorem can be used to justify at least some appeals to popularity as legitimate inferences. More importantly, the conditions for the application of Condorcet’s theorem (binary claim, competent judge, epistemic independence) can be used as critical tools when evaluating appeals to popularity. The application of these three concepts to appeals to popularity provide a more fine-grained critical strategy for argument evaluation and, also, allow us to see the real problems that often arise with such appeals more clearly.